Automatic Bengali image captioning using efficientNet-transformer network and vision transformer - Kabir, Muhammad Khubayeeb; Labonno, Anindita; Amin, Sofia; Tahsin, Fariha (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.